Management and clinical outcomes of cardiogenic shock in King Abdulaziz University Hospital: A retrospective study - Fida, Hamza L.; Qutub, Mohammed A.; Algazzar, Alaa S.; AlDharrab, Abdulrahman S.; Alnajjar, Terad A.; Andijani, Anas M.A.; Taiyeb, Ahmad M. (Saudi medical journal, 2023)
To assess frequencies of various management approaches in cardiogenic shock (CS) and their clinical outcomes. Cardiogenic shock is a state of organ hypoperfusion and hypoxia caused by cardiac failure. In this retrospective record review, we assessed the presentations, vital signs, laboratory readings, and treatments for 188 consecutive CS inpatients from 2010-2021. Patients were labeled as "ischemic CS" or "non-ischemic CS" based on the occurrence of myocardial infarction as the precipitating cause, and "post-operative CS" if they had undergone cardiac surgery. In-hospital mortality was the primary endpoint of the study. We identified 118 (62.8%) ischemic, 64 (34%) non-ischemic, and 6 (3.2%) postoperative CS patients. The study population had a high mortality rate (85.1%). Logistic regression analysis revealed that dopamine ( =0.040) and epinephrine ( =0.001) were independent predictors of mortality, while dobutamine ( =0.004) and digoxin ( =0.044) associated with increased survival. No significant association with mortality was found between either PCI or IABP. No significant difference in mortality was observed between CS subgroups. Variations in outcomes occurred with different medications. Mortality was higher in patients receiving dopamine or epinephrine and lower in those receiving dobutamine or digoxin. Implementation of clinical trials for investigation of the mortality benefit observed with dobutamine can serve towards formulation of new guidelines for improvement of CS mortality rates.